From Silent Learners to Confident Speakers : The Effect of AI Voice Chat with ChatGPT on EFL Speaking Skills - Salsabil, Aisyah Diah; Rakhmawati, Lathifa Aliya; Febtwenesty (Journal of English Education, 2025)
The integration of artificial intelligence tools such as ChatGPT into English as a Foreign Language (EFL) instruction has gained increasing attention for its potential to enhance speaking skills. This study explores EFL students’ perceptions and experiences regarding the use of ChatGPT to develop English-speaking proficiency. This research used mix method with the 60 students at eleventh grade of SMAN 10 Palembang as sample for quantitative, and 5 participants as randomize as participants for the qualitative, to collecting the data used t-test and interview and analysisng data used paired and independents sample t-test and thematic analysis. The findings indicate that students generally perceive ChatGPT positively, reporting improvements in fluency, vocabulary, grammar, and confidence during spoken interactions. ChatGPT’s ability to provide personalized feedback, simulate real-time conversations, and create a low-anxiety environment contributes to its pedagogical value. However, issues such as cognitive load, technological dependence, and limited contextual understanding also emerged as concerns. This study underscores the importance of aligning AI tools with instructional design and learner needs to optimize their effectiveness. It contributes to the growing body of literature on AI in education and offers insights for educators, policymakers, and curriculum designers aiming to incorporate ChatGPT into EFL speaking instruction.